IDENTITY AND COMMUNICATION PATTERN OF BERCO TRIBE IN SUMBAWA REGENCY CONCERNING LAND CONFLICT SITUATION - Anshori, Muhammad Syukron; SF, Aka Kurnia (Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to analyze the communication process of the Berco tribe in Sumbawa Besar that figured in establishing their reality in agrarian conflict. This study is distinctive and novel since the social science approach, including the pattern of communication, symbol, culture, and identity, was used as the approach. This research used a qualitative study with an over-participants approach, and the informants of the study were chosen using goodness criteria with a purposive sampling technique. In analyzing the data, the author used a model of interactive technique by Miles and Huberman that comprised three steps: data collection, data reduction, data display, and conclusion. The results showed that the Berco tribe held their cultural tradition solidly as a way to show their existence during the conflict. Rapulung, or deliberate instruction communication patterns, became a process that is imposed during the conflict. Furthermore, the use of native language, namely 'Berco,' is one of the cultural identities that is considered important as a form of resistance and becomes the individual variability in influencing the choices and strategies in the conflict situations.